Evaluation of Compressive Strength in Various Timbers for Agricultural Implements in Pantnagar, Uttarakhand, India - Annu Rani; Jayant Singh; T.P. Singh; Ajit Kumar; Mukesh Kumar Choudhary (Archives of Current Research International, 2024)
This study investigates the compressive strength of various timber types, including Red Cedar, Java Plum, Mango, Yellow Teak, Margosa, Eucalyptus, Teak, North Indian Rose timber, Lebbeck, and Sal. The compressive strengths of these timbers were measured to be 43.79, 50.42, 78.00, 71.16, 68.32, 69.88, 80.78, 85.50, 65.12, and 81.20 MPa, respectively. North Indian Rose timber and Sal exhibited the highest compressive strengths, suggesting their superior suitability for applications requiring high compressive resistance. Conversely, Red Cedar showed the lowest compressive strength among the timbers tested. The standard deviations for these measurements were Java Plum (0.07), Mango (0.28), Yellow Teak (0.36), Teak (0.45), Margosa (0.52), Eucalyptus (6.11), Red Cedar (0.69), North Indian Rose timber (0.79), Lebbeck (0.93), and Sal (0.68), with Mango displaying the lowest variation. The findings indicate that North Indian Rose timber and Sal are particularly robust, while Mango exhibits consistent compressive strength, making these timbers preferable for specific structural applications.